2023
DOI: 10.20944/preprints202312.0108.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Managing the Intermittency of Wind Energy Generation in Greece

Theodoros Christodoulou,
Nikolaos S. Thomaidis,
Ioannis Pytharoulis
et al.

Abstract: This paper undertakes an in-depth exploration of a primary strategy aimed at mitigating the volumetric risk in wind power generation within Greece, which originates from the variability of wind speeds. The proposed strategy hinges on portfolio theory, serving as the foundation for creating diverse generation portfolios, thus facilitating the strategic distribution of available capacity across space. Optimization techniques and quadratic programming are harnessed to derive the minimum variance portfolio along w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…The data and sources of information used in this study are described as follows 7 : For solar generation, data from the following nine areas are used for each: 1.Hokkaido; 2.Tohoku; 3.Tokyo; 4.Chubu; 5.Hokuriku; 6.Kansai; 7.Chugoku; 8.Shikoku; 9.Kyushu (see Figure 1). On the other hand, for solar radiation, data for one major city in each area is used (1.Sapporo; 2.Sendai; 3.Tokyo; 4.Nagoya; 5.Toyama; 6.Osaka; 7.Hiroshima; 8.Takamatsu; 9.Fukuoka).…”
Section: Data Descriptionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data and sources of information used in this study are described as follows 7 : For solar generation, data from the following nine areas are used for each: 1.Hokkaido; 2.Tohoku; 3.Tokyo; 4.Chubu; 5.Hokuriku; 6.Kansai; 7.Chugoku; 8.Shikoku; 9.Kyushu (see Figure 1). On the other hand, for solar radiation, data for one major city in each area is used (1.Sapporo; 2.Sendai; 3.Tokyo; 4.Nagoya; 5.Toyama; 6.Osaka; 7.Hiroshima; 8.Takamatsu; 9.Fukuoka).…”
Section: Data Descriptionmentioning
confidence: 99%
“…In general, PCA has been employed in the analysis of distributed renewable generation due to its effectiveness in compressing dimensionality and enhancing the understanding of spatial data features [4]. For example, Burke et al [5] found that PCA is effective in limiting the number of random statistical variables needed to represent distributed wind power; Fonseca Junior et al [6] proposed a highly accurate model using PCA to predict solar power generation at local sites in Japan; Christodoulou et al [7] conducted a PC risk analysis of wind power in the context of site selection for wind power investment. As these studies show, PCA exhibits a natural affinity for the analysis of regionally distributed renewable energy generation and holds significant potential for modeling geographic time series data through dimensionality compression.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation